2016
DOI: 10.1080/03014460.2016.1207805
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Cypriot paternal lineages bear an autochthonous character and closest resemblance to those from neighbouring Near Eastern populations

Abstract: Turkish Cypriot paternal lineages seem to bear an autochthonous character and closest genetic connection with the neighbouring Near Eastern populations. These observations are further underscored by the fact that the haplogroups associated with the spread of Neolithic Agricultural Revolution from the Fertile Crescent (E1b1b/J1/J2/G2a) dominate (>70%) the Turkish Cypriot haplogroup distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 44 publications
5
18
0
Order By: Relevance
“…The haplogroup assigning procedure in the TCy sample was initially performed ‘blinded’ to the original study’s haplogroup assignments, in order to avoid ascertainment (assessor) bias in haplogroup assignment. Following the haplogroup assignment in the TCy sample, the results were compared to those from the original study[14] and a very high degree of agreement (S3 Table) was observed, with minor differences being due to the slightly different assigning procedures followed. The Y-STR haplotypes and assigned Y-haplogroups (as well as details for the assigning procedure) for GCy and TCy population samples can be found in S1 and S3 Tables, respectively,…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The haplogroup assigning procedure in the TCy sample was initially performed ‘blinded’ to the original study’s haplogroup assignments, in order to avoid ascertainment (assessor) bias in haplogroup assignment. Following the haplogroup assignment in the TCy sample, the results were compared to those from the original study[14] and a very high degree of agreement (S3 Table) was observed, with minor differences being due to the slightly different assigning procedures followed. The Y-STR haplotypes and assigned Y-haplogroups (as well as details for the assigning procedure) for GCy and TCy population samples can be found in S1 and S3 Tables, respectively,…”
Section: Methodsmentioning
confidence: 99%
“…For comparison purposes, a publicly available Turkish Cypriot (TCy) population sample (n = 380 Y-STR haplotypes)[14] (YHRD accession number: YA003850) was analyzed (S3 Table). Although these TCy haplotypes were assigned haplogroups in silico in the original study using one of the tools used in the current study (Whit Athey’s Predictor), this procedure was repeated, following the same methodology used in the GCy population sample (described in detail above), with the only difference being that no SNP testing was performed, as the actual samples were not available.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations